Trade war between the USA and China: Impact on an Austrian company in the steel sector - Thomas Scheipl; Vito Bobek; Tatjana Horvat (Naše gospodarstvo / Our Economy, 2020)
The paper is intended to provide information on the trade war between China and the USA. It analyses the consequences of the trade dispute, discusses the impact on an Austrian company in the steel sector, gives an overview of possible strategies with which companies can reduce the negative effects of tariffs and discusses strategies that are good options for companies in the steel industry. The methodology applied included theoretical and empirical research based on quantitative analysis as well as quantitative research in the form of expert interviews. The results show that the trade war between China and the USA was in full swing until January 2020. The impacts do not only affect the parties involved, but also other parties such as the EU. Companies can use a variety of strategies to mitigate the negative effects of trade wars. The best strategy for a company depends on the structure of the company, its products and its competitors. The paper adds new insights to the existing literature on the trade war between China and the US and its effects, strategies to mitigate the negative effects of tariffs and discussions on optimal strategies for companies in the steel industry.
Keywords: F13; F51; 330; trade war; China; USA; tariffs; EU; strategies